Effects of fibrolytic enzymes on grass silages, inoculation and storage conditions on whole-plant corn silage, and a meta-analysis of storage temperature in silages - Cruz, Gabriel Ferreira de Lima (2024)
This study was mainly divided into three chapters: Chapter 1 – Two experiments were carried out to evaluate whether the addition of cellulase and/or xylanase enzymes interacts with regrowth age (RA) in mombasa grass and elephant grass cv. BRS Capiaçu to alter nutritive, fermentation profile and ruminal degradation kinetics. Mombasa and elephant grass plots were mowed and harvested at two different RA (7- and 11-wk for mombasa grass; 12- and 16-wk for elephant grass) and submitted to the following additive treatments: no additive (control), xylanase enzyme, cellulase enzyme, and cellulase + xylanase enzymes, in a factorial arrangement of 4 (additives) × 2 (regrowth ages), with three replicates. In both trials, lower degradability was observed for late harvest. For mombasa grass silage, lower DM losses and more extensive fermentation were observed for early harvest, while the opposite was observed for elephant grass silage. Cellulase improves the fermentation profile of Mombasa grass silage, while xylanase enhances the dry matter and neutral detergent fiber degradability of elephant grass silage. The combined application of these enzymes does not appear to warrant recommendation. Chapter 2 – This study evaluated the effects of a heterofermentative inoculant, storage temperature and storage length on fermentation profile, aerobic stability, and nutrient composition of whole-plant corn silage. The experiment was a completely randomized design with a 2 (microbial inoculation) × 2 (storage temperature) × 4 (storage length) factorial arrangement of treatments. Corn forage was either inoculated with distilled water (CON) or with 300,000 CFU/g of fresh forage of Pediococcus acidilactici DSM 16243, Lentilactobacillus buchneri DSM 12856, and L. diolivorans DSM 32074 (LBLD). Silos were stored for 7, 15, 30 or 90 d at either 22 (NT) or 40? (HT). Soluble crude protein and ammonia-N concentrations, and in vitro starch digestibility increased with SL and were greater for silage stored at HT. Inoculation increased pH and LAB counts. Three-way interactions were observed for acetic acid and 1-propanol concentrations, and aerobic stability, which LBLD-22 was greater than other treatments at 90 d. Greater temperature negatively impacted fermentation profile and increased spoilage after aerobic exposure, whereas the heterofermentative inoculant enhanced aerobic stability. However, improvements in fermentation profile and aerobic stability with microbial inoculation were alleviated when silage was stored at greater temperatures. Chapter 3 – A meta-analysis of 42 peer-reviewed articles was conducted to examine the effects of temperature ranges on nutritive and fermentation profile of silage. A complementary meta-analysis of 15 articles examined the effects on whole-plant corn silage (WPCS) specifically. The effects were evaluated by ranges of temperature and the treatments were classified into the following categories: 1) = 10°C; 2) > 10 and = 20°C; 3) > 20 and = 30 °C; 4) > 30 and = 40°C; 5) > 40°C. Overall, The environmental temperature during fermentation affected the activity of LAB, and both high and low temperatures reduced acid production. Therefore, the temperature range of 21-30°C may be more suitable for silage storage and fermentation due to greater total acid production and more rapid decline in pH, which enhances nutrient preservation. Keywords: degradability; fermentation profile; nutritive value.